Quining Ecofeminism: Saintifikasi Keadilan Iklim dan Gender: Quining Ecofeminism: The Saintification of Climate Justice and Gender - Rahima, Raisa (Undiksha, 2024)
Ecofeminism as a theory is far from complete to solve the problems of climate injustice, gender and even other problems that may be under the umbrella of ecofeminism. This article finds that ecofeminism is sufficient as a scientific stance (axiology), but not enough at the epistemic level. The tendency of ecofeminism theorists to characterize the ontology of nature and women: with specific gender or other analogies, instead of focusing on the scope of